replace the third equation by the sum of itself and -1 times the second equation x-2y-7z=17,-6x+4y+5z=-9,8x+7y=z=-4 Question replace the third equation by the sum of itself and -1 times the second equation x-2y-7z=17,-6x+4y+5z=-9,8x+7y=z=-4 in progress 0 Math Autumn 14 mins 2021-10-14T01:01:18+00:00 2021-10-14T01:01:18+00:00 1 Answer 0

## Answers ( )

Answer:Step-by-step explanation:— 1

— 2

—3

-1 times the second equation =

= –4

Now we are given that replace the third equation by the sum of itself and -1 times the second equation

So, New third equation =

=

Hence the new third equation is